Prediction of spoilage of tropical shrimp (Penaeus notialis) under dynamic temperature regimes - Dabadé, D. Sylvain; AZOKPOTA, PAULIN; NOUT, M.J. Robert; ZWIETERING, Marcel H.; HOUNHOUIGAN, DJIDJOHO JOSEPH; DEN BESTEN, Heidy M.W. (My University, 2015)
The spoilage activity of Pseudomonas psychrophila and Carnobacterium maltaromaticum, two tropical shrimp (Penaeus notialis) spoilage organisms, was assessed in cooked shrimps stored at 0 to 28 °C. Microbiological, chemical and sensory analyses were performed during storage. P. psychrophila had a higher growth rate and showed a higher spoilage activity at temperatures from 0 to 15 °C,while at 28 °C, C. maltaromaticumhad a higher growth rate. The spoilage activity of P. psychrophilawas found to be higher in cooked shrimp than in fresh shrimp. Observed shelf-life data of shrimps stored at constant temperatureswere used to validate a previously developed model that predicts tropical shrimp shelf-life at constant storage temperatures. Models predicting the growth of the spoilage organisms as a function of temperature were constructed. The validation of these models under dynamic storage temperatures simulating temperature fluctuation in the shrimp supply chain showed that they can be used to predict the shelf-life of cooked and fresh tropical shrimps.
Keywords: Seafood spoilage; Pseudomonas spp.; Carnobacterium maltaromaticum; Shelf-life prediction; Predictive model